Clinical Outcomes and Patient Experience of Biosimilar to Biosimilar Infliximab Switching in Patients with Inflammatory Bowel Disease: A Prospective, Single-Centre, Phase IV Interventional Study with a Nested Qualitative Study - Clare Harris; Richard James Harris; David Young; Martin McDonnell; Bridget Clancy; Justin Harvey; Carlos Araujo; Ines Iria; Joao Goncalves; Susan Latter; J. R. Fraser Cummings (GastroHep)
Background and Aims. Regulatory pathways compare biosimilars with originator molecules only and not with other biosimilars. With the development of multiple infliximab biosimilars, patients may be asked to transition between them. Data is emerging but there is still a gap in the evidence on switching between infliximab biosimilars. Our aim was to conduct a full evaluation of switching a cohort of IBD patients from one biosimilar (CT-P13) to another (SB2) in a real-world setting including clinical and patient experience and molecular and drug immunogenicity aspects of the process. Methods. Prospective, phase IV interventional study of patients on CT-P13 switched to SB2. Demographics, disease history, validated disease activity scores, PROMs, and laboratory measurements were collected. Semistructured qualitative interviews were also conducted. Results. 133 out of 158 patients agreed to participate. Mean disease duration was 9.2 years. There was no difference in mean haemoglobin, platelet count, albumin, and C-reactive protein before and after switching. Mean faecal calprotectin at baseline and at week 30/32 was 306 μg/g versus 210 μg/g. Mean pMCS and mHBI at baseline were 1.54 and 3.14 versus 1.18 and 2.91 at week 30/32, respectively. Thirty-five subjects discontinued. There were 16 serious adverse events. Thematic analysis identified six major themes that reflected the patient experience—trust, clinical status at the point of switching, past experience, general disposition, information provision, and concerns/anxiety. Conclusions. Switching from CT-P13 to SB2 is safe and effective. Certain factors must be considered in supporting patient decision-making. These results support the development of clear, streamlined, and well-monitored biosimilar switching programmes.